Gambaran Penerapan Protokol Pencegahan Penularan Covid-19 Pada Praktik Dokter Gigi di Kota Samarinda - Rahmah, Fausia; Purnamasari, Cicih Bhakti; Muthi'ah, Nisa (Fakultas Kedokteran, 2022)
The COVID-19 pandemic has greatly affected various health workers, one of which is the practice of dentistry. The possibility of inhalation of aerosols or droplets containing COVID-19 causes the possibility of transmission in dental practice. The purpose of the study was to determine the application of the protocol to prevent the transmission of COVID-19 in dental practice in the city of Samarinda. The research used a descriptive research design. The respondents were selected using a purposive sampling technique as many as 29 respondents. The results showed that the type of health service was teledentistry (41.38%), ART method (37.93%), all respondents screened (100%). Precautionary procedures keep a distance (89.66%), wash hands (96.55%), rubber dam (6.90%), aerosol box (27.59%), HEPA (37.93%), HVE (37, 93%). Waste management categorizes non-medical medical waste (82.76%). Recommend mouthwash before treatment (79.71%) povidone iodine (68.97%), suggest mouthwash at home (62.07%) povidone iodine (48.28%), Chlorhexidine (34.48%). Use of PPE surgical masks, N95 (86.21) faceshield (96.55%), handscoon (93.10%), headcap (79.31%) goggles (55.17%), disposable gown (58.62%) , foot cover (55,17%). All respondents sterilized the instruments (100%) using the autoclave method (58.62%), room sterilization (93.10%) using UV light (37.93%), ethanol as a disinfection solution (86.21%). The conclusion of the study was that less than the average number of respondents carried out teledentistry health services, ART methods, rubber dams, aerosol boxes, HEPA, HVE as preventive measures, goggles, disposable gowns, foot coverings as PPE, while more than the average number of respondents did precautions to keep distance, wash hands, waste management categorize non-medical medical waste, recommend mouthwash before treatment, at home contain povidone iodine, chlorhexidine, PPE surgical masks, N95, faceshield, handscoon, headcap, autoclave method for instrument sterilization, room sterilization , ethanol as a disinfectant, and all respondents screened.Keywords: Dentist Practice, Prevention Protocol, COVID-19 Transmission, Aerosol, Droplet